2017
DOI: 10.1021/acs.jpclett.7b02140
|View full text |Cite
|
Sign up to set email alerts
|

Fingerprints of Both Watson–Crick and Hoogsteen Isomers of the Isolated (Cytosine-Guanine)H+ Pair

Abstract: Gas phase protonated guanine-cytosine (CGH) pair was generated using an electrospray ionization source from solutions at two different pH (5.8 and 3.2). Consistent evidence from MS/MS fragmentation patterns and differential ion mobility spectra (DIMS) point toward the presence of two isomers of the CGH pair, whose relative populations depend strongly on the pH of the solution. Gas phase infrared multiphoton dissociation (IRMPD) spectroscopy in the 900-1900 cm spectral range further confirms that the Watson-Cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
56
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 25 publications
(62 citation statements)
references
References 48 publications
2
56
0
4
Order By: Relevance
“…However, recent NMR studies have observed transient sequence-specific base-pairing other than the WC type, which occurred inside canonical DNA double helixes. 10,11,18 In an extensive exploration of the conformations of [C:G:H] + complexes, proton-bound Hoogsteen conformations were predicted to be the most stable, and they were far more stable than protonated WC base pairs. In particular, base-pairing in proton-bound Hoogsteen base pairs of C and G, [C:G:H] + , involves two hydrogen bonds of which one is ionic.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…However, recent NMR studies have observed transient sequence-specific base-pairing other than the WC type, which occurred inside canonical DNA double helixes. 10,11,18 In an extensive exploration of the conformations of [C:G:H] + complexes, proton-bound Hoogsteen conformations were predicted to be the most stable, and they were far more stable than protonated WC base pairs. In particular, base-pairing in proton-bound Hoogsteen base pairs of C and G, [C:G:H] + , involves two hydrogen bonds of which one is ionic.…”
mentioning
confidence: 99%
“…In particular, base-pairing in proton-bound Hoogsteen base pairs of C and G, [C:G:H] + , involves two hydrogen bonds of which one is ionic. 10,11,18 In an extensive exploration of the conformations of [C:G:H] + complexes, proton-bound Hoogsteen conformations were predicted to be the most stable, and they were far more stable than protonated WC base pairs. Due to the electrostatic interaction, the ionic hydrogen bonding offers a stronger interaction than neutral hydrogen bonding.…”
mentioning
confidence: 99%
See 3 more Smart Citations